Effectiveness of iterative interventions to increase research productivity in one residency program - Richard Alweis; Suzanne Wenderoth; Anthony Donato (Greater Baltimore Medical Center, 2015)
Background: The Accreditation Council for Graduate Medical Education requires residency programs to expose residents to research opportunities. Objective: The purpose of this study was to assess the impact of a series of iterative interventions to increase scholarly activity in one internal medicine residency. Methods: Retrospective analysis of the effectiveness of a series of interventions to increase resident and faculty scholarly productivity over a 14-year period was performed using quality improvement methodology. Outcomes measured were accepted regional and national abstracts and PubMed indexed manuscripts of residents and faculty. Results: Initially, regional meeting abstracts increased and then were supplanted by national meeting abstracts. Sustained gains in manuscript productivity occurred in the eighth year of interventions, increasing from a baseline of 0.01 publications/FTE/year to 1.57 publications/FTE/year in the final year measured. Run chart analysis indicated special cause variation associated with the interventions performed. Conclusions: Programs attempting to stimulate research production among faculty and residents can choose among many interventions cited in the literature. Since success of any group of interventions is likely additive and may take years to show benefit, measuring outcomes using quality improvement methodology may be an effective way to determine success.